INFORMATION SYSTEM FOR AUTOMATIC TRAFFIC LIGHT ALGORITHM REGULATION - KRYVENCHUK, YURII; BOIKIV, MYKOLA; BOIKIV, ROMAN (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This work explores an information system that, based on intelligent analysis of traffic patterns using cameras installed at intersections, allows real-time optimization of traffic light cycle duration, taking into account traffic conditions. One of the priority directions for improving traffic light control at intersections is the use of intelligent systems to enhance the efficiency of traffic flow management. Such an automatic regulation information system, using a camera to adjust the traffic light algorithm, is an innovative solution in traffic management. It utilizes a camera to collect video data from intersections and analyzes them to dynamically adapt the traffic light operation. Through special image processing algorithms, the system determines the traffic intensity in different directions and considers traffic priorities. This enables the optimization of the distribution of time between traffic light phases, ensuring maximum efficiency of traffic movement and reducing congestion. Using an algorithm to calculate the type and quantity of vehicles, the system determines the overall traffic intensity on each approach to the intersection before the stop line. In the event of significant queues on a particular intersection approach, the information system adjusts the traffic light cycle, taking into account traffic conditions, and provides a more efficient passage of traffic through the intersection. The information system for automatic regulation of the traffic light algorithm using a camera implements cutting-edge technologies to enhance road safety and optimize road infrastructure. In general, the system of automatic regulation of traffic light phases with a camera is a promising approach to traffic optimization at intersections and an urgent task to improve the efficiency of urban transport systems.
Keywords: automatic regulation; traffic flow; traffic light regulation; information system; intersection efficiency; road traffic